ANALISIS PERTUMBUHAN PENJUALAN DAN DEBT TO EQUITY RASIO TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SUBSEKTOR PERDAGANGAN BESAR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anton Eka Saputra; Yonson Pane; Muammar Rinaldi (Niagawan, 2022)
This study aims to examine the effect of Sales Growth and Debt to Equity Ratio on Tax Avoidance in the Trade Sector. The population used in this study are large trading sub-sector companies on the Indonesia Stock Exchange for the period 2015 - 2019 totaling 40 companies. This study used a purposive sampling technique which was analyzed using linear regression. The results of the analysis provide evidence that Sales Growth and Debt to Equity Ratio have an effect on Tax Avoidance in Big Trading Subsector companies listed on the Indonesian stock exchange either partially or simultaneously.